Occurrence, Distribution, and Extraction Methods of Microplastics in Marine Organisms - Olubusoye, Boluwatife S.; Oni, Peter; Owusu, Faustina; Adekoya, Oluwatoyin; Ongwech, Acaye; Odogwu, Daniel A.; Awolesi, Oluwafemi; Oje, Ayobami; Arwenyo, Beatrice; Olaleye, Bisola V. (Research Advances in Environment, Geography and Earth Science Vol. 4, 2024)
This study provides a comprehensive overview of the occurrence, distribution, and extraction methods of microplastics in marine organisms to present current data on the presence and distribution of microplastics in marine environments worldwide in a bid to understand the extent of microplastics pollution and their potential effects in marine ecosystems while discussing the pros and cons of different extraction methods of MPs in marine organisms. The widespread presence of microplastics in marine environments has become a significant concern. This chapter reviews the pressing issue of microplastic pollution, its impact on ecosystems, and potential human health risks. Specifically, it addresses the urgent issue of microplastic pollution in marine ecosystems and its potential ramifications for both the environment and human health, providing an overview of the current status of microplastic prevalence, distribution, and extraction methods within marine organisms. Microplastics are recognized as a major environmental problem due to their detrimental effects on ecosystems and their potential risks to human health. These particles enter marine environments through runoff and atmospheric deposition, contaminating beaches and posing threats to marine life. The proliferation of microplastics in aquatic environments represents a multifaceted and pressing environmental challenge. Its repercussions extend well beyond immediate marine ecosystems, impacting the entire ecological food chain and potentially posing risks to human health. Despite the seriousness of this issue, research on the prevalence and distribution of microplastics in marine organisms remains limited. This review seeks to fill this knowledge gap by thoroughly examining the prevalence, distribution, and various extraction methods used to detect microplastics in marine organisms. It stresses the urgent need for targeted measures to manage microplastic pollution, highlights the significant role of human activities in exacerbating this problem, and emphasize the importance of reducing human-induced pollution to protect marine ecosystems. While this review enhances our understanding of microplastic pollution in marine environments and emphasizes the critical need for action to safeguard marine organisms and preserve our oceans for future generations, it also highlights that effectively addressing the microplastic issue requires a well-coordinated approach. This approach should involve research initiatives, policy adjustments, public engagement, and innovative technologies. Crucially, prompt and decisive actions are necessary to counteract the growing threat posed by microplastics to the oceans and the global environment.